2010
DOI: 10.1158/1078-0432.ccr-10-0275
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3β: A Prognostic Marker and a Potential Therapeutic Target in Human Bladder Cancer

Abstract: Purpose: Although recent studies have shown glycogen synthase kinase-3β (GSK-3β), a serine/threonine kinase, as a positive regulator of pancreatic, colon, and kidney cancer cell survival and proliferation, the role of GSK-3 in bladder cancer remains unknown. Our objectives were to determine the subcellular localization of GSK-3β and to evaluate the effect of GSK-3 inhibition in bladder cancer.Experimental Design: We used immunohistochemical staining and nuclear/cytosolic fractionation to determine the expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
78
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 37 publications
(63 reference statements)
8
78
2
Order By: Relevance
“…We demonstrated that GSK3b expression level increased after treatment with quadruplet combination and concordantly b-catenin, CCND1, and c-Myc mRNA levels decreased. The results were not consistent with the results of Naito et al (2010) for bladder cancer cells except for the decrease in the GSK3b mRNA level after unaccompanied TSA treatment. CCND1 and c-Myc are downstream target genes of b-catenin.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…We demonstrated that GSK3b expression level increased after treatment with quadruplet combination and concordantly b-catenin, CCND1, and c-Myc mRNA levels decreased. The results were not consistent with the results of Naito et al (2010) for bladder cancer cells except for the decrease in the GSK3b mRNA level after unaccompanied TSA treatment. CCND1 and c-Myc are downstream target genes of b-catenin.…”
Section: Discussioncontrasting
confidence: 96%
“…GSK3b is recognized as much potential tumor suppressor as GSK3 phosphorylated pro-oncogenic molecules such as c-Jun, c-Myc, CREB, CCND1, and b-catenin. Also, GSK3b is known as tumor promoter for certain cancers, such as prostate and renal cancer (Luo et al, 2007;Naito et al, 2010). Naito et al (2010) showed that GSK3b nuclear expression is associated with high-grade tumors, metastasis, and worse survival in bladder cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It has been reported that SB216763 (ATP-competitive), a GSK3 inhibitor, effectively activated -catenin-mediated transcription. 22 Naito et al 23 showed that GSK3 nuclear expression was associated with highgrade tumors, metastasis, and worse survival in bladder cancer patients. Dose and time-dependent SB216763 improved the cytotoxic effect against the two human urothelial carcinoma cell lines, UMUC3 and UMUC14, suggesting potential therapeutic uses for GSK3 inhibitors.…”
mentioning
confidence: 99%
“…Especially growth factor receptors usually show stronger reactions after shorter incubation times. Nonspecific GSK3α/β inhibition has already shown antitumor potential in various tumor entities including NETs in vitro [14,21] and in vivo [13,15,22,24]. Although IC 50 values seemed rather high for AR-A014418, in all other in vitro studies performed, similar doses (≥5 µM) of AR-A014418 were necessary in order to obtain significant inhibitory effects on cell survival [34,36,46].…”
Section: Discussionmentioning
confidence: 99%